The Muslim question in Europe : political controversies and public philosophies - O'Brien, Peter (2016)
The book challenges the popular notion of a clash of cultures pitting Muslim and non-Muslim Europeans against one another. The study finds instead vehement conflict among three longstanding European public philosophies: liberalism, nationalism, and postmodernism. The consequential differences of outlook are demonstrated in four policy areas: 1) citizenship requirements, 2) the headscarf debate, 3) mosque-state relations and 4) counter-terrorism. The book reaches three important conclusions. First, Muslim Europeans do not represent a monolithic anti-Western bloc – a Trojan Horse – within Europe. They vehemently disagree among themselves but along the same basic liberal, nationalist, and postmodern contours as non-Muslim Europeans. Second, ideological discord significantly contributes to policy “messiness,” that is, to inconsistent, contradictory policies. Third, both the discord and the messiness are remarkably similar from one European country to the next, thereby casting doubt on the dominant theory in comparative migration studies that posits distinct national styles such as French republicanism, German ethno-nationalism and British multiculturalism.